Blaze and the Forest Fire - Anderson, C. W.; Nang Chan Yeema (New York, USA Aladding Paperbacks, 2000)
When Billy and his pony Blaze discover a small forest fire, they ride over a dangerous trail to give the alarm at the nearest farmhouse.
Keywords: Story Collection